THE EFFECT OF MEDIA LEAFLET ASSISTED STAD LEARNING MODEL ON STUDENTS' COGNITIVE LEARNING OUTCOMES AT SMA NEGERI 3 WAINGAPU - Jelita Muluana Rasi Kalli; Anita Tamu Ina; Audrey Louise Makatita (JURNAL EDUSCIENCE, 2023)
This thesis aims to determine the impact of applying the type of STAD assisted through leaflet media on the sophistication of the latest knowledge on the impact of class XI IPA 2 students at SMA Negeri 3 Waingapu. This type of research is an examination with a quantitative strategy, sampling using purposive sampling. The population of this study is all students of class XI IPA SMA Negeri 3 Waingapu even semester 2022/2023. This data pattern is that 36 students of XI IPA 1 experienced improvements due to increased elegance and 36 students of XI Science 2 due to experiments. The consequence of the descriptive assessment obtained stated that the pretest and posttest values for the experimental luxury were 53.52 < 84.58 at the same time as the pretest and posttest scores for the control were 52.69 < 75.83. Then the arrests were examined using paired t samples. the test produces an Asymp sig (2-tailed) of 0.000 which means <0.05. The version of STAD type mastery assisted by leaflet media has an effect on students.Keywords : STAD Version, Leaflets, Cognitive Learning OutcomesÂ AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh model kooperatif tipe STAD berbantuan media Leaflet terhadap hasil belajar siswa kelas XI MIPA2 SMA Negeri 3 Waingapu. Jenis penelitian ini adalah eksperimen dengan pendekatan kuantitatif, pengambilan sampel menggunakan purposive sampling. Populasi dalam penelitian ini adalah seluruh siswa kelas XI MIPA SMA Negeri 3 Waingapu semester genap tahun ajaran 2022/2023. Sampel penelitian ini adalah 36 siswa kelas XI MIPA1 sebagai kelas kontrol dan 36 siswa kelas XI MIPA2 sebagai kelas eksperimen. Hasil analisis deskriptif yang diperoleh menunjukkan bahwa nilai pretest dan posttest kelas eksperimen adalah 53,52 < 84,58 sedangkan nilai pretest dan posttest kelas kontrol adalah 52,69 < 75,83, kemudian dilakukan pengujian hipotesis dengan menggunakan sampel t berpasangan. pengujian menghasilkan nilai Asymp, sig (2-tailed) 0,000 artinya nilai tersebut lebih kecil dari 0,05. Dapat disimpulkan bahwa model pembelajaran kooperatif tipe STAD berbantuan media Leaflet berpengaruh terhadap hasil belajar siswa.Kata Kunci : Model Pembelajaran, STAD, Leaflet, Hasil Belajar